Effect of Entrepreneurial Characteristics, Entrepreneurial Competencies and Business Strategy on Business Performance of Indonesian Companies in Vietnam - Syahputra, Hendra (Digital Repository of Theses - SSBM Geneva, 2024)
Vietnam is one of top destination outbound investment of Foreign Investment and Indonesian companies as well. This research is conducted to investigate factors that impact to business performance that may be contributed to the academic and business practical application on a topic of the effect of Entrepreneurial Characteristics, Entrepreneurial Competencies and Business Strategy on Business Performance in Vietnam. The research is applied to Indonesian companies and affiliates operate in Vietnam which must manage dynamic and high customer requirements with high intensity of competition to win the competition. This research taken in period of October 2022- June 2023 and population of the research is the company leaders who are also the owners and managers of Indonesian companies and affiliates in Vietnam. Use quantitative research by using multiple linier regression analysis technic through hypothesis test with SPSS software to proof effect of vii entrepreneurial characteristics, entrepreneurial competencies, and business strategy on business performance of Indonesian companies in Vietnam. This dissertation succeeds to proof entrepreneurial characteristics, entrepreneurial competencies, and business strategy simultaneously give significant impact on Indonesian companies’ business performance in Vietnam.